Perlindungan Hukum Bagi Pekerja UD. Alam di Banjar Pendem Kabupaten Jembrana - I Komang Angga Triyadi Giri; I Nyoman Putu Budiartha; Luh Putu Suryani (Warmadewa Press, 2021)
Every job has its own risk, including the quiet work of UD. Natural. This study aims to determine the form of legal protection of UD. Nature in carrying out his work accident insurance. This type of research uses empirical law. The results showed that the form of legal protection is the responsibility of UD. Nature that has been given to workers in the form of economic protection where workers are given a district / city minimum wage (UMK), technical protection where workers are given time to adjust to the tools used in companies that are not yet commonly used, and social protection where the UD. Nature pays for medical treatment and provides compensation in the form of cash, if one of her employees has a work accident. Until now, UD. Alam has not registered his workers in the work accident insurance program so that the work accident insurance program at UD. Alam Banjar Pendem Jembrana Regency has not been implemented effectively. Then, economic factors become an obstacle to UD. Alam has not registered its workers into the work accident insurance program, this is due to the heavy burden borne by employers to pay work accident insurance contributions and also the procedures for applying for work accident insurance are always hampered by incomplete requirements so it takes too long to register workers into the work accident insurance program.